Learning to fly : practical knowledge management from leading and learning organizations - Collison, Chris (Capstone Publishing Ltd. ChichesterGB, 2004)
Shares experiences from a wide range of the world's leading knowledge management organizations. Includes tips to enable managers to put knowledge management practices into action.